An investigation of the pharmacokinetics and potential metabolites of potassium 2-((4-amino-5-(morfolinometyl)-4H-1,2,4-triazol-3-yl)thio) acetate on rats - Shcherbyna, R. О.; Щербина, Роман Олександрович (My University, 2020)
The purpose of this work is to study the designated pharmacokinetic parameters and possible metabolites of the substance potassium 2-((4-amino-5-(morfolinometyl)-4H-1,2,4-triazol-3-yl)thio)acetate by intragastric introduction to rats.
Keywords: 1,2,4-triazole; metabolite; pharmacokinetics